Comparative study of the structural, mechanical, electronic, optical and thermodynamic properties of superconducting disilicide YT2Si2 (T=Co, Ni, Ru, Rh, Pd, Ir) by DFT simulation. (July 2023) - Atikur Rahman, Md; Hasan, Mahbub; Lubna, Jannatul Ferdous; Khatun, Rukaia; Sarker, Sushmita; Hasan, Md Zahid; Hossain, Aslam; Hossain, Md Mukter; Rasheduzzaman, Md; Hasan, Wakil; Jamila, Nusrat
Abstract: DFT simulation-based ab -initio approach has been executed for examining the relative physical properties of superconducting disilicide materials YT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir). This is the first comparative theoretical investigation of these materials, which is done through Cambridge Serial Total Energy Package module. Extremely good relation has been observed between the synthesized and calculated structural parameters of all the superconductors. Mechanical structural stability of all the phases has been confirmed from the investigated elastic stiffness parameter. The phonon dispersion curve indicates that the YT2 Si2 compounds with T = Co, Ni, Ru, and Ir are dynamically stable, but those with T = Rh and Pd are dynamically unstable. The investigated elastic moduli show good agreement with previously calculated data where available. Also, the fundamental polycrystalline features such as bulk modulus, shear modulus, Young's modulus, Pugh's and Poison's ratios, ductile/brittle nature and hardness of superconducting YT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir) have been examined. Ductile nature of YRh2 Si2, YPd2 Si2 and brittle nature of YCo2 Si2, YNi2 Si2, and YIr2 Si2 have been observed from analyzing of polycrystalline elastic parameters where YRu2 Si2 lies on the border line of ductile/brittle nature. The high bulk modulus, Young's modulus, and hardness of YIr2 Si2 ensured that this phase has high ability to resist volume and plastic deformation and suitable in industrial applications. On the other hand, the small Young's modulus of YPd2 Si2 ensured its application as a thermal barrier coating (TBC) material. Metallic nature of YT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir) has been confirmed from the band structure and DOS calculations. Mulliken atomic populations and charge density map reveal the existing of covalent and ionic bond inYT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir). Different optical features like dielectric function, refractive index, photo conductivity, reflectivity, absorption and loss function of YT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir) have been executed through CASTEP code directly. The elevated reflectivity in the UV energy site of these phases ensured their application as good solar reflector in this energy site. Furthermore, the thermodynamic properties of superconducting YT2 Si2 (T = Co, Ni, Ru, Rh, Pd, Ir) have been determined from the elastic stiffness constants. The high conductivity of YCo2 Si2 is ensured from its high Debye and melting temperature. The minimum thermal conductivity of YPd2 Si2 ensured that it is suitable to use as a thermal barrier coating (TBC) material. Highlights: Structural properties such as lattice parameters and cell volume have been investigated. Structural stability of the studied compounds has been investigated by phonon calculations. Single and polycrystalline Elastic constants and hardness have been calculated. Electronic properties included band structures, DOS, and charge densities have been studied. The photon related optical properties are investigated. Thermal properties such as Debye temperature, melting point and thermal conductivity are studied.